Toothpick Colon Injury Mimicking Colonic Diverticulitis - Jo, Min Hyeong (Ann Coloproctol, 2018)
Although toothpick ingestion is rare, it can lead to fatal complications in the gastrointestinal tract. Diagnosing toothpick ingestion is difficult because most patients do not recall swallowing one. We report 2 cases of toothpick-ingestion-induced colon injury, mimicking diverticulitis. The first patient was a 47-year-old male who had received conservative treatment under the impression of his having diverticulitis in the cecum. Ultrasonography revealed a linear foreign body in the right lower abdomen; a subsequent laparoscopic examination revealed inflammation around the cecum, but no evidence of bowel perforation. A thorough investigation revealed a toothpick embedded in the subcutaneous fat and muscle layer of the lower abdominal wall; we removed it. The second patient was a 56-year-old male who had received conservative treatment under the impression of his having diverticulitis in the sigmoid colon. An explorative laparotomy revealed a toothpick piercing the sigmoid colon; we performed an anterior resection. Both patients were discharged without postoperative complications.